2012
DOI: 10.1002/smll.201290110
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery: Hollow Copper Sulfide Nanoparticle‐Mediated Transdermal Drug Delivery (Small 20/2012)

Abstract: W. Lu and co‐workers apply hollow copper sulfide nanoparticles with intense photothermal conversion effects for thermal ablation of the stratum corneum through instantaneous heat conduction from an NIR laser. , application of a nanosecond‐pulsed laser provides short lasing periods but extremely high local temperatures, with focused thermal ablation of the stratum corneum, limiting the heat transfer to deep tissue. Thermal ablation‐induced microscale defects are confined within the lasing area. The extent of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Under the chosen conditions the patch can be indeed used for a least a week safely. It has been previously demonstrated that photo-thermal ablation using pulsed rather than continuous laser light produces instant heating, which ceases at the end of each light pulse, resulting in much less temperature increase in the skin and favorable release [55]. In addition, the release profile of ODS under laser pulses of 100 ms, with a dead time of 500 ms, has been examined ( Fig.…”
Section: Release Of Ondansetron (Ods) From Ods Kapton/rgo Patchesmentioning
confidence: 99%
“…Under the chosen conditions the patch can be indeed used for a least a week safely. It has been previously demonstrated that photo-thermal ablation using pulsed rather than continuous laser light produces instant heating, which ceases at the end of each light pulse, resulting in much less temperature increase in the skin and favorable release [55]. In addition, the release profile of ODS under laser pulses of 100 ms, with a dead time of 500 ms, has been examined ( Fig.…”
Section: Release Of Ondansetron (Ods) From Ods Kapton/rgo Patchesmentioning
confidence: 99%
“…At room temperature, the DOX-loaded Cu 39 S 28 -FA remained loaded at pH 7.4, and only less than 10 % DOX was released in 24 h. In pH 5.0 buffer, DOX was quickly released to 32 % of the original amount in the first 8 h, and ~45% in 24 h. This pH responsive controlled-release property can be attributed to the dissociation of electrostatic interaction between the positively-charged DOX molecules and negatively-charged Cu 39 S 28 -FA HNPs, due to the weak electrostatic interaction of DOX with COO − and the enhanced solubility of DOX under lower pH environment. 4042 The Cu 39 S 28 -FA HNPs can effectively leak DOX during the blood circulation and increase the delivery efficacy in cancer cells. Moreover, the release profiles at 37 °C was also tested (Figure S5), which was a reflection of actual physiological environment.…”
Section: Resultsmentioning
confidence: 99%
“…and carbon NPs have been used for TDD because of their advantages of nearinfrared (NIR) absorption, adjustable size, large surface area-to- volume ratio, easy synthesis, and surface functionalization. [92][93][94][95][96] Haine et al demonstrated the feasibility of transdermal delivery of ovalbumin (OVA) and OVA epitope peptides mediated by the photothermal effect of PTET in Au nanorods. 94 Similarly, PTET in hollow CuS NPs developed by Lu's group 97 achieved good results.…”
Section: Ptet In Thermal Ablationmentioning
confidence: 99%